Effect of several reaction parameters in the solvent-free ethyl oleate synthesis using Candida rugosa lipase immobilised on polypropylene - Foresti, María Laura (2005)
Lipase from Candida rugosa was immobilised onto polypropylene powder by physical adsorption. The immobilised catalyst (CR/PP) was used in the enzymatic synthesis of ethyl oleate in solvent-free medium. The influence of the initial water content, acidity of the aqueous media added, mass of catalyst, reaction temperature, substrate ratio, etc., on enzymatic activity, has been studied. Comparison of specific enzymatic activities achieved using the prepared catalyst and the crude lipase demonstrated that C. rugosa lipase was interfacially activated upon its adsorption on polypropylene. Besides, immobilisation of the lipase led to enhanced thermal stability. Experimental data reported in this manuscript do not belong to equilibrium data but to enzymatic activity attained in the first 2 h of reaction. After this period, it was shown that, in the current synthesis, deactivation/agglomeration/inhibition of the catalyst prevented further CRL activity. However, 2 h measurements allowed fulfilling the aim of this work: the determination of the best conditions for ethyl oleate production in short periods of time, using an immobilised derivative of a relatively cheap lipase as it is C. rugosa lipase. Best results were achieved in the reaction performed at 45°C and 350 rpm, with an initial stoichiometric ratio of substrates, 20% of aqueous content, and mediated by 50 mg of CR/PP (0.0585 mmol/mg of CR-h). The deleterious effect of ethanol excess and agglomeration of the native and immobilised catalyst have been analysed. © 2005 Elsevier B.V. All rights reserved.